PSYCHOLOGICAL EFFECTS OF GIVING MANIPULATION MASSAGE BEFORE AND AFTER THE EXERCISE (ON ATHLETES BADMINTON CLUB CITRA RAYA UNESA) - MUKIN, (Jurnal Prestasi Olahraga, 2013)
the psychological aspect of athlete is often ignored by the coach and the athlete  itself when they do the exercise, whereas psychological aspect is really important for the athlete itself for getting a good physical and psychological condition. Even the athlete has prepared their selves as well as possible, but lacks of encouragement to their performance often lead of disappointing results. In this case, it is important to maintain of the physical and psychological condition during exercising. Giving of massage manipulation can influence the psychological condition. Thus, the manipulation of massage does not only influence their physiological, biological and reflektoris, but also the psychology of the athlete itself. The researcher used a quantitative research by exploring his experiment. This research aims to find out the psychology effects of giving massage manipulation before and after exercising to the athlete of badminton club Citra Raya UNESA. The subjects of this study are 30 members of badminton club Citra Raya UNESA. The researcher?s instrument of his research was a questionnaire form. The results showed that there was an influence of manipulation massage before and after exercising for badminton Club Citra Raya Unesa athletes :T table or  T count or 3,724 ? 1,699. Almost all of athletes of badminton club Citra Raya UNESA agree about giving massage manipulation before and after exercising because it gives benefit to the athlete psychologist before and after exercising.   Keywords: Effect Psychologist, Massage, Exercise.